The use of cinnamon powder in the diet of Japanese laying quail - Thailine Santana Santos; Claudia da Costa Lopes; Gregório Murilo Oliveira Junior; Luziane Moreira Santos; Camilla Cristina Santos Santana; Douglas Melo Souza (Acta Scientiarum. Animal Sciences, 2019)
The objective of this study was to evaluate the inclusion of powder cinnamon in the diet of Japanese quails, regarding their performance and egg quality. A total of 360 quails, 18 weeks old, were distributed in a completely randomized design with five treatments and six replicates of 12 animals. The experimental period lasted 84 days. The treatments were the inclusion of 0; 3.0; 6.0; 9.0 and 12.0 g kg-1 of cinnamon powder in the diet. The performance and quality of eggs produced were evaluated. A sensorial analysis of the eggs was carried out to evaluate the color of the egg yolk, the taste of the egg and the purchase intention. There was no significant effect on the performance and egg quality variables, except for the specific gravity and color of the yolk, which increased linearly. The evaluators presented a higher intention to purchase eggs from the treatment with 6g kg-1 of cinnamon addition in the diet. We concluded that the inclusion of 12.0 g kg-1 of cinnamon powder in the diet for laying quail does not affect the performance and the taste of the eggs, nevertheless, this level of inclusion provides an improvement in the specific gravity and color of the yolk.